Peningkatan Kemampuan Guru Dalam Proses Pembelajaran Berkualitas Melalui Supervisi Akademik Dengan Teknik Kunjungan Kelas pada Guru Sekolah Dasar - Ninik Sriwahyuni T (Universitas Sebelas Maret, 2019)
The purpose of this study was to improve the ability of Surodadi 1 Elementary School teachers in quality learning through academic supervision with the technique of visiting the first semester of the school year 2018/2019. The study was conducted by taking the subject of teachers at Surodadi 1 Elementary School 1 totaling 12 people consisting of 10 classroom teachers and 2 subject teachers where the researchers were principals. This research was conducted for 4 months starting in July 2018 s, in October 2018.The method used in this study is the school action research method which consists of 2 cycles, each cycle consisting of 4 stages, namely planning, implementation, observation and reflection. Data obtained in the form of observation of learning devices, learning and assessment process learning in cycle 1 and cycle 2. Data analysis was done by comparative descriptive analysis that is comparing the results of observations of cycle I and cycle II. Keywords: teacher competence, quality learning, academic supervision of class visit techniques